Is the Fourth Industrial Revolution a window of opportunity for upgrading or reinforcing the middle-income trap? Asian model of development in Southeast Asia. Issue 4 (1st October 2020) - Lee, Keun; Wong, Chan-Yuan; Intarakumnerd, Patarapong; Limapornvanich, Chaiyatorn
ABSTRACT: This paper focuses on the cases of Malaysia and Thailand and investigates the possibility of upgrading these countries from the middle-income trap and the possible roles of the 4th Industrial Revolution (4IR) in this process. The 4IR may induce firms to introduce factory automation to facilitate upgrade into higher segments with local spillovers. A key factor for this positive scenario is local institutions facilitating the training and upskilling of their local workforce. By contrast, increased problems are expected for other countries with the mid-range level of wages and mid-level of educated population, and firms in these economies mostly execute labor-intensive production and are likely to be substituted by additional factory automations or their multinational firms may move to neighboring countries for low wages.